Metabolic stability and metabolite profiling of emerging synthetic cathinones - Lopes, Rita P.; Ferro, Raquel A.; Milhazes, Margarida; Figueira, Margarida; Caldeira, Maria João; Antunes, Alexandra M. M.; Gaspar, Helena (Frontiers in Pharmacology, 2023)
Synthetic cathinones constitute the second largest groups of novel psychoactive substances (NPS), which are especially popular among adolescents and young adults. Due to their potential toxicity, the recreational use of these NPS constitute a serious worldwide public health problem. However, their fast appearance in the market renders the continuous updating of NPS information highly challenging for forensic authorities. The unavailability of pharmacokinetic data for emerging NPS is critical for forensic and clinical verifications. With the ultimate goal of having a proactive approach towards the NPS issue, high resolution mass spectrometry was used in the current work to assess preliminary pharmacokinetic data for 8 selected cathinones: 4 reported substances (4-CIC, 3-CMC, 4-CMC and 4-MEAP) and 4 previously unreported ones (3-CIC, 4-MDMB, 4-MNEB and 4-MDMP) for which the emergence on the NSP market is expected to be eminent, were also included in this study. Based on the calculation of pharmacokinetic parameters, half-life and intrinsic clearance, 4-CMC and 4-MDMB are low and high clearance compounds, respectively, and all the remaining cathinones included in this study are intermediate clearance compounds. This fact anticipates the key role of metabolites as suitable biomarkers to extend detection windows beyond those provided by the parent cathinones. Reduction of the keto group and hydroxylation on the alkyl chains were the common metabolic pathways identified for all cathinones. However, the relative importance of these metabolic transformations is dependent on the cathinone substituents. The glucuronic acid conjugation to metabolites stemming for keto group reduction constituted the sole Phase II transformation identified. To our knowledge, this study constitutes the first metabolite profiling of the already reported synthetic cathinones 4-CIC, 3-CMC and 4-CMC. Noteworthy is the fact that 3-CMC accounts for almost a quarter of the quantity of powders seized during 2020. The analytical methods developed, and the metabolites characterized, are now available to be included in routine screening methods to attest the consumption of the 8 cathinones studied.